The Impact of Improving Employee Skills and Knowledge Facing Digital Transformation at BSI Bank, Palopo City Branch - Gita Pratiwi Sultan; Altri Wahida; Jusman (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of employee skills and knowledge on digital transformation at Bank Syariah Indonesia (BSI) Palopo City Branch. Digital transformation in the banking sector requires human resources who are capable of operating technology and adapting to new systems. The study used a quantitative approach, involving all 30 employees of BSI Palopo Branch as a sample through census sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results showed that employee skills and knowledge have a positive and significant effect on digital transformation. Knowledge is the most dominant factor in supporting the success of service digitalization. These findings emphasize that improving competency and understanding of technology is essential to strengthen human resource readiness in facing digital changes in Islamic banking